Diabetes predicts severity of COVID‐19 infection in a retrospective cohort: A mediatory role of the inflammatory biomarker C‐reactive protein - Koh, Huilin; Moh, Angela Mei Chung; Yeoh, Ester; Lin, Yi; Low, Serena Kiat Mun; Ooi, Say Tat; Tan, Seng Kiong; Lin, Jaime Hui Xian; Hoong, Caroline Wei Shan (Journal of medical virology, 2021)
Diabetes is a risk factor for developing severe COVID‐19, but the pathogenesis remains unclear. We investigated if the association of diabetes and COVID‐19 severity may be mediated by inflammation. We also hypothesized that this increased risk may extend to prediabetes. Hospitalized patients in Singapore with COVID‐19 were subdivided into three groups in a retrospective cohort: normoglycemia (HbA1c: ≤5.6%), prediabetes (HbA1c: 5.7%–6.4%) and diabetes (HbA1c: ≥6.5%). The primary outcome of severe COVID‐19 was defined by respiratory rate ≥30, SpO2 ≤93% or intensive care unit admission. The association between clinical factors on severe COVID‐19 outcome was analyzed by cox regression. Adjusted mediation analysis of C‐reactive protein (CRP) on the relationship between diabetes and severe COVID‐19 was performed. Of 1042 hospitalized patients, mean age 39 ± 11 years, 13% had diabetes, 9% prediabetes and 78% normoglycemia. Severe COVID‐19 occurred in 4.9% of subjects. Compared to normoglycemia, diabetes was significantly associated with severe COVID‐19 on both univariate (hazard ratio [HR]: 9.94; 95% confidence interval [CI]: 5.54–17.84; p < .001) and multivariate analysis (HR: 3.99; 95% CI: 1.92–8.31; p < .001), while prediabetes was not a risk factor (HR: 0.94; 95% CI: 0.22–4.03; p = .929). CRP, a biomarker of inflammation, mediated 32.7% of the total association between diabetes and severe COVID‐19 outcome. In conclusion, CRP is a partial mediator of the association between diabetes and severe COVID‐19 infection, confirming that inflammation is important in the pathogenesis of severe COVID‐19 in diabetes. Research Highlights Inflammation, as measured by the biomarker C‐reactive protein, partially mediates the association between diabetes and adverse COVID‐19 outcomes, including the risk of developing severe COVID‐19, dyspnea, need for intensive care unit and length of stay. Level of glycaemia in patients with diabetes does not correlate with severe COVID‐19. Prediabetes is not an adverse prognostic marker in COVID‐19.